We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
45
4
avatar+36 

Hi there.

 

I was trying to solve the following question:

 

Part 1

        P2

 

I completed part (i), by showing that dy/dx is equal to the stated above.

 

However, when I attempted part (ii), I got only one coordinate (1, -2), (I equated dy/dx = -1).

 

How would I go about finding the other coordinate?

 

Thank you so much in advance.

Bryan.

 Mar 25, 2019
edited by bqrs01  Mar 25, 2019
 #1
avatar+27653 
+3

Perhaps this graph will help:

 

 Mar 25, 2019
 #2
avatar+36 
+1

Thank you so much for your answer.

 

I have a further question, though. How would I determine this other coordinate if I didn't have access to a graph?

 

Is it possible though algebra alone? If so, could you please show me how? 

 

Thanks once again in advance.

 

Bryan

bqrs01  Mar 25, 2019
 #3
avatar+99351 
+3

x^2 + 2xy

________  =   -1

y^2  - x^2

 

 

x^2  + 2xy  =  -1 ( y^2 - x^2)

 

x^2 + 2xy   =  x^2 - y^2

 

2xy   =  -y^2

 

y^2 + 2xy = 0

 

y ( y + 2x)  =  0        set both factors to  0

 

y = 0      and subbing this into the original equation  produces  

 

x^3  =  3

 

x=  (3)^(1/3)

 

So...another  point  is  ( 3^(1/3) , 0 )

 

 

 

cool cool cool

 Mar 25, 2019
edited by CPhill  Mar 25, 2019
 #4
avatar+21977 
+1

I was trying to solve the following question:

\(\begin{array}{|rcll|} \hline x^2(x+3y)-y^3 &=& 3 \\ x^3 + 3x^2y-y^3 - 3 &=& 0 \\\\ \mathbf{f(x,y)} & \mathbf{=} & \mathbf{x^3 + 3x^2y-y^3 - 3} \\\\ \dfrac{\partial f} {\partial x} &=& 3x^2+6xy \\ \dfrac{\partial f} {\partial y} &=& 3x^2-3y^2 \\ && \boxed{\text{Formula: }\\ \dfrac{dy}{dx} = -\dfrac{\dfrac{\partial f} {\partial x}} {\dfrac{\partial f} {\partial y}} } \\ \dfrac{dy}{dx} &=& -\dfrac{ 3x^2+6xy } { 3x^2-3y^2 } \\\\ \dfrac{dy}{dx} &=& -\dfrac{ 3(x^2+2xy) } { 3(x^2-y^2) } \\\\ \dfrac{dy}{dx} &=& -\dfrac{ x^2+2xy } { x^2-y^2 } \\\\ \mathbf{ \dfrac{dy}{dx}} &\mathbf{=}& \mathbf{\dfrac{ x^2+2xy } { y^2-x^2 }} \\ \hline \end{array}\)

 

laugh

 Mar 26, 2019

10 Online Users